What is the best site for central venous catheter insertion in critically ill patients? - Timsit, Jean-François (BioMed Central, 2003)
The choice of the best central venous access for a particular patient is based on the rate and the severity of failures and complications. Based on two recent papers, internal jugular access is associated with a low rate of severe mechanical complications in the intensive care unit as compared with subclavian access, and it is preferable for short-term access (<5–7 days) and for haemodialysis catheters. Subclavian access is associated with a lower risk for infection and is the route of choice, in experienced hands, if the risk for infection is high (central venous catheter placement >5–7 days) or if the risk for mechanical complications is low. The femoral route is associated with a higher risk for infection and thrombosis (as compared with the subclavian route). It should be restricted to patients in whom pneumothorax or haemorrhage would be unacceptable.